FEM verification of accelerated vibration test method based on Grms - T curve. (February 2022) - Wang, Li-Jun; Wang, Zhi-Wei
Accelerated random vibration test is now the important dynamic performance and safety evaluation technique for transport packaging system during transportation. The current widely used time scale of accelerated random vibration test in engineering test and some standards is "Inverse power law, " which is based on Basquin (power function) fatigue damage model andσ − N curve, but is not completely suitable for transport packaging system. In author's previous research, the general theory of accelerated random vibration test based on acceleration PSD andG rms − T curve was developed which is applied for any fatigue damage model besides Basquin type. The study in this paper is the further and extensive research of previous research. The definite expression between response von Mises equivalent stress (σ eq, rms ) of the products and tri-axial acceleration Root-Mean-Square (RMS) was developed, based on whichσ − N curve was transformed toG rms − T curve to describe the product damage. Time scale of accelerated random vibration was obtained. The proposed method was verified by finite element analysis. In addition, the effects of excitation spectrum shape and system damping on the response vibration of products were discussed. This study is valuable in engineering for safety assessment and random vibration analysis of transport packaging system.